2020
DOI: 10.1038/s12276-020-0475-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DANCR and miR-320a suppressed osteogenic differentiation in osteoporosis by directly inhibiting the Wnt/β-catenin signaling pathway

Abstract: Our study aimed to determine how lncRNA DANCR, miR-320a, and CTNNB1 interact with each other and regulate osteogenic differentiation in osteoporosis. qRT-PCR and western blotting were performed to determine the expression of DANCR, miR-320a, CTNNB1, and the osteoporosis- or Wnt/β-catenin pathway-related markers T-cell factor 1 (TCF-1), runt-related transcription factor 2 (RUNX2), alkaline phosphatase (ALP), osteocalcin (OCN), and osteopontin (OPN). Interactions between CTNNB1, DANCR, and miR-320a were predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…DANCR is a recently identified 8.3-kb lncRNA located on Chromosome 4, consisting of five exons. DANCR was revealed to repress osteogenic differentiation in osteoporosis through inhibiting β-catenin expression [30]. In addition, DANCR expression was found upregulated in circulating monocytes, and increase their bone-resorbing activities in osteoporotic patients and identified as a potential biomarker of postmenopausal osteoporosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…DANCR is a recently identified 8.3-kb lncRNA located on Chromosome 4, consisting of five exons. DANCR was revealed to repress osteogenic differentiation in osteoporosis through inhibiting β-catenin expression [30]. In addition, DANCR expression was found upregulated in circulating monocytes, and increase their bone-resorbing activities in osteoporotic patients and identified as a potential biomarker of postmenopausal osteoporosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging research has illustrated the significance of lncRNAs as important regulators in osteoclastogenesis and osteoblast differentiation. They can play a vital role by regulating cell structural integrity, controlling subcellular localization and inducing epigenetic modification (20)(21)(22). For example, lncRNA SNHG1 has been revealed to attenuate osteogenic differentiation via the miR-101/DKK1 axis in hBMSCs (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-320a is also a microRNA which was associated with the growth and development of osteoblasts. There is study revealed that the expression of miR-320a and lncRNA DANCR relieved the symptoms of osteoporosis by suppressing the Wnt/β-catenin pathway (Wang et al, 2020a). However, there is also study suggested that the expression of miR-320a was promoted in postmenopausal osteoporosis and miR-320a could induce the oxidative damage of osteoblasts by suppressing the PI3K/AKT signaling pathway (De-Ugarte et al, 2018; Kong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-320a is also a microRNA which was associated with the occurrence and development of osteoporosis (Wang et al, 2020a). Moreover, the expression of miR-320a is increased in postmenopausal women with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%